Teachers' response to STEAM-based media for improving Riau Malay culture learning quality - Hermita, Neni; Diniya, Diniya; Dipuja, Diah Anugrah; Nasien, Dewi; Wijaya, Tommy Tanu (Directorate of Research and Community ServiceUniversitas Negeri Yogyakarta, 2024)
STEAM-based learning (Science, Technology, Engineering, Arts, and Mathematics) is a learning approach that combines these five fields of science in one learning activity. This approach aims to develop students' critical thinking, creative and problem-solving skills. The current study seeks to analyze teacher responses in implementing STEAM-based learning media to improve the quality of learning in Riau Malay Culture subjects. This research was conducted using a qualitative approach. Data was collected through questionnaires distributed to elementary school teachers who teach Riau Malay Culture subjects in Pekanbaru City, Riau. The research results show that teachers have a positive response to the implementation of STEAM-based learning media. Teachers assess that STEAM-based learning media can improve the quality of learning in Riau Malay Culture subjects. This is because STEAM-based learning media can make learning more interesting, interactive and meaningful for students. However, it should be noted that teachers are necessary to possess a deep understanding of the STEAM approach in order to pursue effective implementation. Therefore, there needs to be support from the school in providing the facilities and infrastructure needed to implement STEAM-based learning media.